A simple embedded-seeding method to prepare silicalite-1 membrane on porous α-Al2O3 hollow fibers - Sun, M.; Wang, X.; Meng, B.; Tan, X.; Liu, Shaomin (Elsevier BV, 2017)
High quality silicalite-1 membrane was successfully synthesized on the external surface of ceramic hollow fibers by a novel embedded-seeding method. The samples were characterized by XRD, SEM and gas permeation test. It is shown that the obtained silicalite-1 membrane was dense and continuous, with a thickness of about 4–5 µm. Specifically, silicalite-1 membrane exhibited high H2 and N2 permeances of 8.3 × 10-6 and 2.4 × 10-6 mol·m-2·s-1·Pa-1 with good H2-N2 perm-selectivity of 3.45. More finger-like pores in the hollow fibers minimized the gas transport resistance through the support, which is one of the reasons that the prepared supported silicalite-1 membrane is highly permeable.